2001
DOI: 10.1051/parasite/2001084267
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of a proteasome inToxoplasma gondii: intracellular localization and specific peptidase activities

Abstract: Summary :The proteasome is a large intracellular protein complex whose main function is proteolytic removal of damaged proteins. It has recently been shown that the proteasome has a crucial role in the pathogenesis of protozoan parasites. We attempted to characterize the proteasome of T. gondii (RH strain). In immunoblot experiments, we showed that MCP231 monoclonal antibody, directed against the human 20S proteasome, labelled homologous proteins in T. gondii with a pattern similar to that observed in mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The proteasome has several peptidase activities, of which the most extensively investigated is ''chymotrypsin-like'', as it cleaves substrates on the carboxyl side of a hydrophobic residue. In a previous study (Paugam et al 2001), we obtained similar K m and specific activity values for Toxoplasma and HeLa proteasomes with Suc-LLVY-AMC (0.06 mM, 0.08 mM; 16.7 pmol, 32 pmol min -1 mg -1 , respectively). No published data are available on gliotoxin inhibition of protozoan parasites.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The proteasome has several peptidase activities, of which the most extensively investigated is ''chymotrypsin-like'', as it cleaves substrates on the carboxyl side of a hydrophobic residue. In a previous study (Paugam et al 2001), we obtained similar K m and specific activity values for Toxoplasma and HeLa proteasomes with Suc-LLVY-AMC (0.06 mM, 0.08 mM; 16.7 pmol, 32 pmol min -1 mg -1 , respectively). No published data are available on gliotoxin inhibition of protozoan parasites.…”
supporting
confidence: 74%
“…It has recently been shown that progression through the life-cycle of various protozoan parasites like Entamoeba (Gonzalez et al 1999), Leishmania (Robertson 1999), and Trypanosoma (de Diego et al 2001) requires a functional proteasome. We have previously demonstrated the presence of a proteasome in T. gondii by intracellular localization and detection of specific peptidase activity (Paugam et al 2001); and proteasome inhibitors have been tested for the treatment of malaria in an experimental model (Gantt et al 1998). Following the recent demonstration that fungal gliotoxin efficiently inhibits the proteasome (Kroll et al 1999), we studied the effect of gliotoxin on the proteolytic activity of the Toxoplasma proteasome and on Toxoplasma infectivity in vitro.…”
mentioning
confidence: 98%
“…2D). As T. gondii is known to have proteasomes 23, 24, there was a possibility that the enhanced activity was due to increased activity of T. gondii proteasomes. Therefore, we collected T. gondii from each preparation but could not detect proteolytic activity in the parasites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The T. gondii proteasome contains homologues of many components found in other eukaryotes, and additional proteins unique to T. gondii (Paugam et al, 2003; Paugam et al, 2001). The T. gondii genome possesses a conserved and functional repertoire of ERAD proteins (Agrawal et al, 2009), a large number of candidate ubiquitin ligases and deubiquitinases, as well as ubiquitin and ubiquitin-like modifiers (Ponder and Bogyo, 2007; Ponts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%